Perancangan Sistem E-Voting Berbasis Website Pada Pemilihan Ketua Umum HIMTIF Universitas Pamulang - Putri Salimah Auliany Wijanarko; Bambang Santoso (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The advancement of internet technology has had a significant impact on communication and information provision. HIMTIF at Pamulang University is an organization that focuses on developing knowledge and skills in the field of information technology, including through HPC (HIMTIF Programming Camp) activities that deepen programming languages. This research uses the extreme programming (XP) method in system development. XP is used because it is a simplified software development method and can adapt to various conditions. From the results of the research conducted, it is proven to be able to produce an effective and efficient system because the election results can be directly processed and the results can be immediately known who will become the next student council chairman. This system is also able to run well in accordance with testing using the blackbox method that has been carried out. This system has also proven to be able to facilitate students in making choices because it can be done from school or from home and is environmentally friendly because the use of paper is not needed as much as when the election is still done manually. The implementation of e-voting in the election of the chairman and vice chairman of HIMTIF was successfully carried out by providing benefits in improving the efficiency and security of the election process. E-voting allows wider participation with online voting and maintains the confidentiality of user data through encryption and authentication methods. For further development, it is recommended that the system can be used by the entire Student Association, maintaining the principle of vote confidentiality, improving authentication accuracy with IP, and developing Android-based applications for easier access.